Effect of Orientation program on Hemodynamic Variables of Patients Undergoing Heart Catheterization - Nasrin Hanifi; Nasrin Bahraminejad; Saide Amane Idea Dadgaran; Fazlollah Ahmadi; Mohammad Khani; Saide Fatemeh Haghdoost Oskouie (Tehran University of Medical Sciences, 2011)
Background & Aim: Physiologic signs of anxiety usually change hemodynamic variables in patients undergoing heart catheterization. This study carried out to determine the effect of Orientation Program on hemodynamic variables in patient undergoing heart catheterization. Methods & Materials: In this experimental study, 60 patients undergoing heart catheterization were randomly assigned to either the test or control group. Data were collected using the demographic checklist and a hemodynamic variables checklist for recording hemodynamic variables. The collected data were analyzed using the Chi-square, repeated measurement, and independent t test in the SPSS. Results: According to the results, there were significant reductions in the systolic and diastolic blood pressures, pulse rate, respiratory rate and systolic left ventricle pressure in the intervention group after the intervention (P<0.05). There were no significant statistical difference between the two groups in systolic aorta pressure (P=0.173), diastolic aorta pressure (P=0.104), and end diastolic left ventricle pressure (P=0.886). Conclusion: Orientation program had positive effects on most of the hemodynamic variables in the intervention group. The Orientation program is recommended to be used during invasive diagnostic procedures in order to prohibit anxiety&aposs physiologic complications.